Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite

Domain size manipulation of perflouorinated polymer electrolytes by sulfonic acid-functionalized MWCNTs to enhance fuel cell performance - Kannan, Ramaiyan; Parthasarathy, Meera; Maraveedu, Sreekuttan U.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Langmuir, 2009)
The application of sulfonic acid-functionalized multiwalled (s-MWNT) carbon nanotubes to manipulate the hydrophilic domain size of Nafion membranes is explored here as an option for tuning the proton conductivity of polymer electrolyte membranes for hydrogen-oxygen fuel cells. The electrochemical impedance experiments provide preliminary evidence of increased proton conductivity, while small-angle X-ray scattering measurements line. out enhanced ionic cluster domain size in these composite membranes as the central reason for higher conductivity (70 angstrom for the optimum composite membrane vs 50 angstrom for Nafion 115) values. Scanning electrochemical microscopy indicates synergistic interaction between the sulfonic acid functional groups present in the Nation membrane and those on the nanotube surface. More interestingly, the nanotube-tailored Nafion membranes ameliorate the performance of fuel cells as confirmed by measurements at a sin le-cell level, which reveal a maximum power density of 380 mW cm(-2), higher than those of Nafion 115 (250 mW cm(-2)) and recast Nafion (230 mW cm-2) membranes. Thus, in addition to providing an elegant means of controlling the ionic cluster size, the strategic approach of using CNT both as an anchoring backbone for -SO(3)H groups to enrich proton conductivity and as a blending agent to improve the mechanical characteristics of the Nafion phase might be helpful in alleviating many critical problems associated with the use of commercial Nafion membranes.

Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

Distinctive PdCl2-mediated transformation of Fe-based metallogels into metal-organic frameworks - Aiyappa, Harshitha Barike; Saha, Subhadeep; Garai, Bikash; Thote, Jayshri; Kurungot, Sreekumar; Banerjee, Rahul (Crystal Growth & Design, 2014)
Simple, efficient conversion of viable Fe3+-based metallogels into Fe-metal-organic frameworks (MOFs) has been achieved by PdCl2-mediated gel degradation. The metallogels and the resulting MOFs have been characterized, and a probable mechanism for the event has been elucidated.

On demand electrochemical release of drugs from porous reduced graphene oxide modified flexible electrodes - Boulahneche, Samia; Jijie, Roxana; Barras, Alexandre; Chekin, Fereshteh; Singh, Santosh K.; Bouckaert, Julie; Medjram, Mohamed Salah; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
Despite the advantages of an electrochemical control for drug release, only a handful of electrochemical-based release systems have been developed so far. We report herein on the development of an electrochemically activatable platform for on-demand delivery of drugs. It is based on flexible gold thin film electrodes coated with porous reduced graphene oxide (prGO) nanosheets onto which the drug of interest has been integrated beforehand. Two different drugs are investigated here: ondansetron hydrochloride (ODS), a selective 5-HT3 receptor antagonist used for preventing nausea and vomiting caused by chemotherapy and radiotherapy, and ampicillin (AMP), an antibiotic to prevent and treat a number of bacterial infections such as respiratory tract infections, urinary tract infections, and meningitis. In the case of ODS, application of a negative potential bias of -0.8 V results in a sustained slow ODS release with an ODS flux of 47 mu g cm(-2) h(-1). In the case of AMP, we show that polyethyleneimine modified prGO (prGO/PEI) is an extremely efficient matrix. Upon the application of +0.8 V, 24% of AMP could be released from the electrical interface in a time span of 2 h. The released AMP kept its antibacterial activity as demonstrated by antimicrobial tests. These examples illustrate the major benefits of the developed approach for biomedical applications.

Dendrite growth suppression by Zn2+-integrated nafion ionomer membranes: beyond porous separators toward aqueous Zn/V2O5 batteries with extended cycle life - Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy Technology, 2019)
The dendritic/irregular growth of zinc deposits in the anode surface is often considered as a major intricacy limiting the lifespan of aqueous zinc-ion batteries. The effect of separators on the evolution of the surface morphology of the anode/cathode is never thoroughly studied. Herein, for the first time, the efficacy of the Zn2+-integrated Nafion ionomer membrane is demonstrated as a separator to effectively suppress the growth of irregular zinc deposits in the metallic anode of an aqueous Zn/V2O5 battery. The Zn2+-ions coordinated with the SO3- moieties in Nafion result in a high transference number of the Zn2+ cation, all the while facilitating a high ionic conductivity. The Zn2+-integrated Nafion membrane enables the Zn/V2O5 cell to deliver a high specific capacity of 510 mAh g(-1) at a current of 0.25 A g(-1), which is close to the theoretical capacity of anhydrous V2O5 (589 mAh g(-1)). Moreover, the same cell exhibits an excellent cycling stability of 88% retention of the initial capacity even after 1800 charge-discharge cycles, superior to that of the Zn/V2O5 cells comprising conventional porous separators.

Dioxolanone-anchored poly(allyl ether)-based cross-linked dual-salt polymer electrolytes for high-voltage lithium metal batteries - Vijayakumar, Vidyanand; Diddens, Diddo; Heuer, Andreas; Kurungot, Sreekumar; Winter, Martin; Nair, Jijeesh Ravi (ACS Applied Materials & Interfaces, 2020)
Novel cross-linked polymer electrolytes (XPEs) are synthesized by free-radical copolymerization induced by ultraviolet (UV)-light irradiation of a reactive solution, which is composed of a difunctional poly(ethylene glycol) diallyl ether oligomer (PEGDAE), a monofunctional reactive diluent 4-vinyl-1,3-dioxolan-2-one (VEC), and a stock solution containing lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in a carbonate-free nonvolatile plasticizer, poly(ethylene glycol) dimethyl ether (PEGDME). The resulting polymer matrix can be represented as a linear polyethylene chain functionalized with cyclic carbonate (dioxolanone) moieties and cross-linked by ethylene oxide units. A series of XPEs are prepared by varying the [O]/[Li] ratio (24 to 3) of the stock solution and thoroughly characterized using physicochemical (thermogravimetric analysis-mass spectrometry, differential scanning calorimetry, NMR, etc.) and electrochemical techniques. In addition, quantum chemical calculations are performed to elucidate the correlation between the electrochemical oxidation potential and the lithium ion-ethylene oxide coordination in the stock solution. Later, lithium bis(fluorosulfonyl)imide (LiFSI) salt is incorporated into the electrolyte system to produce a dual-salt XPE that exhibits improved electrochemical performance, a stable interface against lithium metal, and enhanced physical and chemical characteristics to be employed against high-voltage cathodes. The XPE membranes demonstrated excellent resistance against lithium dendrite growth even after reversibly plating and stripping lithium ions for more than 1000 h with a total capacity of 0.5 mAh cm(-2). Finally, the XPE films are assembled in a lab-scale lithium metal battery configuration by using carbon-coated LiFePO4 (LFP) or LiNi0.8Co0.15Al0.05O2 (NCA) as a cathode and galvanostatically cycled at 20, 40, and 60 degrees C. Remarkably, at 20 degrees C, the NCA-based lithium metal cells displayed excellent cycling stability and good capacity retention (>50%) even after 1000 cycles.
Keywords: cross-linked polymer electrolyte; dual-salt electrolyte; high-voltage cathode; lithium metal battery; solvent-free photopolymerization

Defect-rich CoFe-alloy with engineered carbon support for high-performance rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Barik, Sidharth; Torris, Arun; Maria, Anit; Kumar, Yogesh; Kurungot, Sreekumar (Small, 2025)
Defect-rich CoFe-alloy with engineered carbon support is synthesized as a bifunctional cathode, coupled with a modified electrode fabrication technique, for rechargeable zinc-air batteries (RZABs). The CoFe(2:1)/N-rGCNT-catalyst is synthesized by annealing graphene oxide (GO), cobalt and iron acetate, and melamine, leading to the in situ formation of CoFe alloy-encapsulated CNTs. This resulted in a unique layer-separated Fe-rich skin@CoFe alloy decorated nitrogen-doped graphene (NGr) with CoFe-encapsulated CNTs. The interplay of line defects, enhanced conductivity, and electronic modulation underpins electrocatalyst's performance. Electrochemical analysis revealed an onset potential of 955 mV vs RHE, a half-wave potential of 835 mV vs RHE for oxygen reduction reaction (ORR) and an overpotential of 340 mV for oxygen evolution reaction (OER), yielding a Delta E of 0.73 V, comparable to the reported catalysts. The 3D X-ray microtomography simulations suggest improved air permeability of CoFe(2:1)/N-rGCNT facilitates easier gas diffusion, contributing in better device performance. The RZAB with CoFe(2:1)/N-rGCNT-cathode exhibited a peak power density of 171.3 mW cm(-)2, surpassing 140.8 mW cm(-)2 obtained from a cell based on Pt/C-cathode. The Co/N-rGCNT-based battery achieved a stable discharge profile at 10 mA cm(-)2 with a specific capacity of 650 mAh g(-)(1)Zn, and in rechargeable mode, achieved 140 h of high-rate charge-discharge cycling capability.
Keywords: 3D tomography; N-doping; alloy encapsulated structure; device demonstration; grain boundaries; oxygen reduction and evolution reactions; rechargeable zinc-air battery